Enhanced cholesterol-dependent hemifusion by internal fusion peptide 1 of SARS Coronavirus-2 compared to its N-terminal counterpart - Pattnaik, Gourab Prasad (2021)
Membrane fusion is an important step for the entry of the lipid-sheathed viruses into the host cells. The fusion process is being carried out by fusion proteins present in the viral envelope. The class I viruses contains a 20-25 amino acid sequence at its N-terminal of the fusion domain, which is instrumental in fusion, and is termed as ‘fusion peptide’. However, Severe Acute Respiratory Syndrome Coronavirus (SARS) coronaviruses contain more than one fusion peptide sequences. We have shown that the internal fusion peptide 1 (IFP1) of SARS-CoV is far more efficient than its N-terminal counterpart (FP) to induce hemifusion between small unilamellar vesicles. Moreover, the ability of IFP1 to induce hemifusion formation in-creases dramatically with growing cholesterol content in the membrane. Interestingly, IFP1 is capable of inducing hemifu-sion, but fails to open pore.